OPTIMIZATION OF TREATMENT TACTICS FOR ANEMIA IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Melikoziev Xurshidbek Bahromjon o’g’li. (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Anemia secondary to chronic kidney disease (CKD) profoundly accelerates renal function decline and amplifies cardiovascular morbidity, demanding highly calibrated therapeutic interventions rather than broad-spectrum erythropoiesis stimulation. This study systematically deconstructs the heterogeneity of hematological responses by evaluating 80 CKD stage 3-5 patients sequentially admitted to the therapeutic facilities of the Andijan State Medical Institute. Following a rigorous 12-week optimized protocol integrating intravenous iron sequencing prior to judicious erythropoiesis-stimulating agent (ESA) administration, clinical evaluations yielded an escalated mean hemoglobin concentration of 11.2 ± 0.8 g/dL from a baseline of 8.6 ± 1.1 g/dL (p < 0.001). Crucially, multivariable logistic regression modeling isolated distinct efficacy deterrents that actively manipulate the erythropoietic trajectory. Pre-existing severe systemic inflammation, indicated by elevated high-sensitivity C-reactive protein (hs-CRP > 5.0 mg/L), yielded a 3.2-fold higher probability of severe ESA hyporesponsiveness. Conversely, preemptive correction of absolute iron deficiency drastically blunted the required cumulative ESA dosing. Ultimately, mitigating inflammatory barriers and optimizing iron-hepcidin pathways are urgent prerequisites to maximizing hemopoietic efficacy. These empirical findings mandate a definitive departure from homogenized, dose-escalation protocols toward highly stratified, predictive clinical models tailored to individual ferrokinetic profiles.